Lipid-polycaprolactone Core-shell Hybrid Nanoparticles for Controlled Delivery of Nateglinide - Das, Malay K. (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: Lipid-polymer hybrid nanoparticles (LPHNPs) combine the biomimetic advantages of lipids and the structural benefits of polymers. The aim of the present study is the development of core shell LPHNPs encapsulating a model lipophilic drug nateglinide and perceived its controlled delivery. Materials and Methods: LPHNPs were prepared by single emulsion solvent evaporation method using polycaprolactone as polymer and glyceryl monostearate, palmitic acid, and lauric acid as lipid. The formulations were characterized in terms of particle size, zeta potential, drug entrapment efficiency, drug loading (DL), surface morphology, in vitro drug release, and release kinetics studies. Results: Dynamic light scattering analysis demonstrated the smaller particle size of LPHNPs (380.2 ± 3.5–544.7 ± 2.8 nm) as compared to polycaprolactone polymeric NPs (PNPs) (647.1 ± 1.9–675.8 ± 3.7 nm). Transmission electron microscopy images of LPNPs and PNPs demonstrate that they are spherical in shape. The entrapment efficiencies (84.9 ± 0.1–87.76 ± 0.23%) and DL capacity (4.63 ± 0.01–8.18 ± 0.09%) of LPHNPs were higher than PNPs (72.5 ± 0.1% and 2.05 ± 0.005%). The higher colloidal stability of LPHNPs was confirmed by their zeta potential value at -12.5 ± 2.1––33.4 ± 0.2 mv as compared to zeta potential of PNPs (–8.71 ± 0.3–9.60 ± 0.1 mv). The LPHNPs displayed a biphasic drug release pattern with an initial burst release, followed by controlled release. The LPHNPs demonstrated the slower drug release (60–70% at 24 h) than that from PNPs (90% at 24 h). Conclusion: The results suggest the controlled release behavior of nateglinide from the developed lipid-polymer core shell hybrid NPs. The developed nanocarriers hold the great promise for controlled delivery of both the lipophilic and hydrophilic drugs to improve their pharmacokinetics.